Carbonized Silk Nanofiber Membrane for Transparent and Sensitive Electronic Skin - Wang, Qi; Jian, Muqiang; Wang, Chunya; Zhang, Yingying (Advanced functional materials, 2017)
Recent years have witnessed the explosive development of electronic skin. Highly sensitive pressure sensing is one of the primary abilities of electronic skin. To date, most of the reported skin‐like pressure sensors are based on nanomaterials and microstructured polydimethylsiloxane (PDMS) films, limiting their wide practical applications due to the unknown biotoxicity and the redundant fabrication procedure. A cost‐effective, large‐area‐capable, and biocompatible approach for fabrication of high‐performance skin‐like pressure sensors is highly desired. Silk fibroin (SF) is a natural protein that has recently drawn great attention due to its application as the substrate for flexible electronics. Here, the fabrication of skin‐like pressure sensors is demonstrated using SF‐derived active materials. Flexible and conformal pressure sensors can be fabricated using transparent carbonized silk nanofiber membranes (CSilkNM) and unstructured PDMS films through a cost‐effective and large‐scale capable approach. Due to the unique N‐doped carbon nanofiber network structure of CSilkNM, the obtained pressure sensor shows superior performance, including ultrahigh sensitivity (34.47 kPa−1) for a broad pressure range, an ultralow detection limit (0.8 Pa), rapid response time (<16.7 ms), and high durability (>10 000 cycles). Based on its superior performance, its applications in monitoring human physiological signals, sensing subtle touch, and detecting spatial distribution of pressure are demonstrated. Using carbonized electrospun silk nanofiber membranes and planar polydimethylsiloxane films, a skin‐like ultrasensitive pressure sensor is fabricated. The sensor shows superior performance, including high sensitivity (34.47 kPa−1), an ultralow detection limit (0.8 Pa), fast response time (<16.7 ms), and high stability and durability (>10 000 cycles), enabling its wide application in real‐time biomedical monitoring and smart equipment.